2023
DOI: 10.3390/app13063552
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Vibro-Acoustics Optimization of a Car Body Rear Part

Abstract: The perceived vibro-acoustic comfort, inside the passenger compartment, under driving conditions, is strictly related to the car body torsional behavior. The aim of this work was to identify which parts of a car body most influence the first torsional mode, in order to modify them and acquire an increase in such car body natural frequency. It was also intended to exploit the great potential of 3D printing that allows an increase in the complexity of component shapes, with an acceptable compromise with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Based on the inertia release method, the body-in-white stiffness simulation was carried out by NASTRAN software [12] . The simulation results showed that the comfort stiffness, first-order torsion, and first-order longitudinal bending of the integral die-cast aluminum were better than those of the traditional steel structural parts.…”
Section: Stiffness Analysis Of the Body In Whitementioning
confidence: 99%
“…Based on the inertia release method, the body-in-white stiffness simulation was carried out by NASTRAN software [12] . The simulation results showed that the comfort stiffness, first-order torsion, and first-order longitudinal bending of the integral die-cast aluminum were better than those of the traditional steel structural parts.…”
Section: Stiffness Analysis Of the Body In Whitementioning
confidence: 99%